2009
DOI: 10.1159/000235551
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a 2,4-Dinitrochlorobenzene-Induced Chronic Dermatitis Model in Rats

Abstract: Although many mouse models of atopic dermatitis have been reported, few rat models have been studied. In this study, a rat chronic allergic dermatitis model was developed and evaluated as a pharmacological model of atopic dermatitis. Prominent ear thickening and scratching were induced after the application of 2,4-dinitrochlorobenzene to the right ear of Brown Norway rats 3 times per week for 3 weeks. Histopathologically, infiltration of T cells in the ear was observed on day 7, and eosinophils and mast cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 72 publications
1
30
0
Order By: Relevance
“…The dermatitis model also showed an increase in scratching behavior but now accompanied by lower mechanical thresholds. This hypersensitivity indicates that the application of dinitrochlorobenzene to induce itch also induced inflammation, as noted previously (Fujii et al, 2009;Park and Oh, 2014). The CFA model showed a significant increase in mechanical sensitivity without an increase in scratching behavior, indicating that this model induced inflammation without itch (Hossaini et al, 2010).…”
Section: Itch and Hypersensitivitysupporting
confidence: 78%
See 1 more Smart Citation
“…The dermatitis model also showed an increase in scratching behavior but now accompanied by lower mechanical thresholds. This hypersensitivity indicates that the application of dinitrochlorobenzene to induce itch also induced inflammation, as noted previously (Fujii et al, 2009;Park and Oh, 2014). The CFA model showed a significant increase in mechanical sensitivity without an increase in scratching behavior, indicating that this model induced inflammation without itch (Hossaini et al, 2010).…”
Section: Itch and Hypersensitivitysupporting
confidence: 78%
“…In this study, we investigated the changes in the density of peptidergic and non-peptidergic fibers occurring in the epidermis and upper dermis during chronic itch and during chronic inflammation using three different animal models: the dry skin model (Akiyama et al, 2010), which has been shown to induce itch without inflammation, the dermatitis model (Fujii et al, 2009), which induces itch accompanied by inflammation, and the complete Freund's adjuvant (CFA) model, which is widely used as a model of chronic inflammation without itch (Stein et al, 1988;Hossaini et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, skin and immunological alterations in DNCB-induced dermatitis were similar to those observed in human AD [24,25,26], including clinical features such as skin erosion, hemorrhage, edema, and increased serum IgE levels [27]. Therefore, the DNCB-induced BALB/c mice model was adopted to evaluate the effects of SBT oil on AD in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…DNCB is an extensively studied animal model of AD and is preferred due to its reproducibility and repeatability. 22,23) In this study, we investigated the inhibitory effect of eriodictyol on DNCB-induced AD-like skin lesions in ICR mice. We separated the groups into control, AD-like model, and eriodictyol treatment groups.…”
Section: Discussionmentioning
confidence: 99%